Adolescents’ health literacy perspectives and implications - Adamu Amanu Asari; Zewdie Birhanu; Ameyu Godesso (BMC Public Health)
Abstract Background Adolescence is an essential stage of life during which individuals develop knowledge, attitudes, and behaviors that can have significant impacts on their present and future health. Therefore, health literacy issue among adolescents is a pressing matter. Understanding adolescents’ perspectives of health literacy is crucial for making informed interventions. However, the topic remains unexplored in developing countries like Ethiopia. This study seeks to explore adolescents’ perspectives of health literacy within their socio-environmental context in Ethiopia and draw out the implications. Methods This study employed qualitative research approach, utilizing in-depth interviews and focus group discussions as methods of data collection. Data collection took place from March to October 2023, involving 86 participants (41 male and 45 female) selected through purposive sampling (maximum variation sampling) to capture a wide range of perspectives on the issue. The data analysis followed a thematic analysis approach, using Atlas.ti (version 7.5.18) software. Results From the adolescents’ perspectives, health literacy or being health literate is regarded as comprising various competencies and qualities essential for health, including health awareness and knowledge, abilities to deal with health information, practicing healthy behaviors, upholding healthy norms and values of the community, and being a responsible citizen. The adolescents regard health literacy or being health literate as highly beneficial in healthcare, disease prevention, health maintenance and enhancement, and in taking responsibility not only for ones’ own health but also for the health of others, thereby benefiting those around them and their community and society. However, this study found notable gaps in health literacy among the adolescents, influenced by various factors ranging from individual to community and societal levels. Conclusion The study explored health literacy from adolescents’ perspectives in Ethiopia, and contributed to understanding of the issue. It identified notable gaps in adolescent health literacy and provided insights into the enabling and hindering factors. This study laid the ground for developing a health literacy tool sensitive to the Ethiopian sociocultural context and for broader studies to enhance understanding and to develop effective interventions to improve and promote health literacy among adolescents and within the broad society.